Comparison of ozone and thermal hydrolysis combined with anaerobic digestion for municipal and pharmaceutical waste sludge with tetracycline resistance genes. (1st August 2016) - Pei, Jin; Yao, Hong; Wang, Hui; Ren, Jia; Yu, Xiaohua
Abstract: Biosolids from wastewater treatment plant (WWTP) are environmental reservoirs of antibiotic resistance genes, which attract great concerns on their efficient treatments. Anaerobic digestion (AD) is widely used for sewage sludge treatment but its effectiveness is limited due to the slow hydrolysis. Ozone and thermal hydrolysis pre-treatment were employed to improve AD efficiency and reduce antibiotic-resistant genes in municipal and pharmaceutical waste sludge (MWS and PWS, respectively) in this study. Sludge solubilization achieved 15.75–25.09% and 14.85–33.92% after ozone and thermal hydrolysis, respectively. Both pre-treatments improved cumulative methane production and the enhancements were greater on PWS than MWS. Five tetracycline-resistant genes ( tet (A), tet (G), tet (Q), tet (W), tet (X)) and one mobile element ( int I1) were qPCR to assess pre-treatments. AD of pre-treated sludge reduced more tet genes than raw sludge for both ozonation and thermal hydrolysis in PWS and MWS. Thermal hydrolysis pre-treatment was more efficient than ozone for reduction after AD. Results of this study help support management options for reducing the spread of antibiotic resistance from biosolids. Graphical abstract: Highlights: Ozone and thermal hydrolysis pre-treatments were employed to improve AD efficiency. Pre-treatments were more efficiency to improve AD of PWS than MWS. Thermal hydrolysis was more efficient for reduction of tet genes than ozonation. Most tet genes were reduced by thermal hydrolysis but rebounded during AD. Tet genes reacted differently during various processes due to the host microbe.